Cutler Beard Procedure for Bilateral Upper Eyelid Coloboma in Charge’s Syndrom: Surgical Outcome - Aulia, Nur; Pagarra, Halimah; Amir, Suliati P.; Pratiwi, A.; Akib, Marliyanti N. (Syntax Corporation Indonesia, 2024)
Ocular coloboma is one of the anomalies that commonly seen in CHARGE syndrome. This syndrome is an autosomal dominant malformation which includes six major features: coloboma, heart defect, atresia of the choanae, retarded growth and development delay, genital hypoplasia, ear anomalies. Cutler-Beard procedure is one of the major technic when a total or near total upper eyelid is missing. To report the surgical outcome in bilateral upper eyelid coloboma in CHARGE syndrome patient after Cutler Beard’s procedure. A 8 month-old boy presented to the hospital with bilateral upper eyelid coloboma since birth. Other clinical manifestations including bilateral optic nerve coloboma, external ear anomalies, bilateral undecensus testis, growth and developmental delay, and CHARGE facies which were consistent with 2 and 4 major and minor diagnostic criteria. The patient underwent eyelid reconstruction by using Cutler Beard procedure in both of eyes. Cutler Beard procedure may be used as the primary reconstruction method in bilateral upper eyelid coloboma in CHARGE syndrome.